Potential impact of mammal defaunation on the early regeneration of a large-seeded palm in the Brazilian Atlantic Forest - Ana Y. Y. Meiga; Alexander V. Christianini (Neotropical Biology and Conservation, 2020)
Defaunation, the decline in animal species and populations, is biased towards large-bodied animals that have unique roles as dispersers of large seeds. However, it is speculated that these roles may still be performed by smaller animals, such as small mammals like rodents and marsupials, that thrive in defaunated sites. We investigated if small mammals can disperse the large-seeded palm Attalea dubia. We performed the study in a well-conserved Atlantic Forest remnant in southeast Brazil that still harbours large mammals, such as tapirs. Focal observations showed that capuchin-monkeys consumed the mesocarp of the fruits and dropped the seeds beneath the plant crown thereafter. Mammals preyed on ca. 1% and removed ca. 15% of the fallen fruit/seed and deposited them up to 15 m away. Amongst them, small mammals (< 1 kg), such as the squirrel Guerlinguetus brasiliensis and non-identified nocturnal Sigmodontinae, as well as the marsupial Philander frenatus performed the bulk of interactions. Dispersal enhances recruitment, but the short distances of seed removal did not match the current spatial distribution of palm seedlings and juveniles. Recaching rates of hoarded seeds were small (2%) and unlikely to increase distances of seed dispersal achieved. Short distances of dispersal would increase plant clumpiness and negative density-dependent effects with time. Although small mammals can provide legitimate dispersal, they cannot fully replace larger frugivorous mammals and maintain long-distance seed dispersal that feeds plant metapopulation dynamics and seed gene flow.